The Relationship between Health Literacy and Blood Sugar Control in Patients with Type II Diabetes Mellitus at the Pekkabata Health Center Polewali Mandar - Wahab, Masyitah; Nurfadhila, Nurfadhila; Fatmawati, Agustina (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Health literacy is an important factor in improving self-care management in DM sufferers. Health literacy is also closely related to blood sugar control. Someone who has adequate health literacy will make patients involved in decision making, maintain their health and have better treatment, thus contributing to improving health. Therefore, improving self-care management requires good health literacy in order to prevent further complications in DM sufferers. Blood sugar control is an indicator of the quality of life for individuals with diabetes because good blood sugar control is one of the parameters of successful lifestyle. This study aims to determine the relationship between health literacy and blood sugar control in people with type II diabetes mellitus at the Pekkabata Polewali Mandar Community Health Center. This type of research is quantitative research using a cross-sectional approach. The population in this study were DM patients at the Pekkabata Polewali Mandar Community Health Center. The sampling technique used in this research was consecutive sampling technique. The data analysis method uses univariate and bivariate analysis using the Chi Square test at a confidence level of 95% (α=0.05). The research results showed a significant relationship between Health Literacy and blood sugar control in Type II Diabetes Mellitus sufferers (p=0.031). The conclusion of this research is that a person's Health Literacy greatly influences the level of health experienced by individuals, especially T2DM sufferers